2005
DOI: 10.1097/01.tp.0000161247.61727.67
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Bone Marrow Transplantation Induces Kidney Allograft Tolerance Across a Full Major Histocompatibility Complex Barrier in Swine

Abstract: The authors demonstrate conclusively that in utero transplantation of fully MHC-mismatched bone marrow in swine can lead to engraftment and stable multilineage hematopoietic chimerism and tolerance to postnatal donor MHC-matched kidney transplantation without the need for immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…These results are consistent with numerous previous reports that hematopoietic chimerism observed naturally in twin gestations (30) and following in utero transplantation in multiple animal models (3,5,14,31,32) and in humans (33) can lead to donor-specific tolerance. Thus, fetal tolerance induction for stem cell transplantation remains an important and approachable clinical goal.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with numerous previous reports that hematopoietic chimerism observed naturally in twin gestations (30) and following in utero transplantation in multiple animal models (3,5,14,31,32) and in humans (33) can lead to donor-specific tolerance. Thus, fetal tolerance induction for stem cell transplantation remains an important and approachable clinical goal.…”
Section: Discussionsupporting
confidence: 82%
“…In the murine model of allogeneic IUHCT, when transplants have been performed at E14-E15, numerous studies have reported failure of engraftment or of only microchimerism (26-34), inconsistent or absent tolerance induction (26,31,35), or immunization to alloantigen after IUHCT (30,33). Similarly, studies of organ transplantation after IUHCT with minimal levels of chimerism in large animal studies have shown an absence of tolerance (36), incomplete tolerance (37), or donor-specific tolerance (38). Interpretation of the results from both the murine and large animal studies has been complicated by marginal levels of engraftment or concerns about inconsistent delivery of donor cells to the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] This tolerance can facilitate postnatal cellular or organ transplantations with minimal or no myeloablative or immunosuppressive conditioning. 3,4,[6][7][8][9][10][11][12][13][14][15] Although engraftment of allogeneic or xenogeneic cells has been achieved, the levels of donor-cell chimerism in most circumstances following IUHCT alone have been below what would be considered therapeutic for most target diseases. [3][4][5][6][7][16][17][18][19][20][21] Additionally, the frequency of engraftment following IUHCT of allogeneic or xenogeneic cells has also been relatively low.…”
mentioning
confidence: 99%